VD_FINDINFO Jug / 2019 / 333 vom 18. Februar 2019 - VD Tribunal cantonal (2019)
VIOLATION DU SECRET DE FONCTIONDROIT PÉNAL, EXCUSABILITÉ, CONSTATATION DES FAITS, ACQUITTEMENT | 14 CP, 320 CP, 398 al. 3 let. b CPP (CH), 420 CPP